1996
DOI: 10.1364/ao.35.005155
|View full text |Cite
|
Sign up to set email alerts
|

Special configuration of a very large Schmidt telescope for extensive astronomical spectroscopic observation

Abstract: A special reflecting Schmidt telescope is used to observe celestial objects. The telescope has an aperture of 4m, f ratio of 5, and a 5° field of view. Its optical axis is fixed and tilted 25° to the horizontal that runs from south to north. The celestial objects were observed for 1.5 h as they passed through the meridian. The shape of the reflecting Schmidt plate has to be changed with each different declination δ and in the tracking process. This is achieved with active optics. The sky area to be observed is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
156
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 255 publications
(160 citation statements)
references
References 10 publications
0
156
0
Order By: Relevance
“…WD J0308+5140 is the only target that we observed that does not fall within the SDSS footprint; it was instead originally identified from a LAMOST (Large Sky Area Multi-Object Spectroscopy Telescope; Wang et al 1996;Cui et al 2012) spectrum. For convenience, we follow the convention of Gianninas et al (2015) and include it in tables under the "SDSS" column header.…”
Section: Wd J0308+5140mentioning
confidence: 99%
“…WD J0308+5140 is the only target that we observed that does not fall within the SDSS footprint; it was instead originally identified from a LAMOST (Large Sky Area Multi-Object Spectroscopy Telescope; Wang et al 1996;Cui et al 2012) spectrum. For convenience, we follow the convention of Gianninas et al (2015) and include it in tables under the "SDSS" column header.…”
Section: Wd J0308+5140mentioning
confidence: 99%
“…The Large Sky Area Multi-Object Fiber Spectroscopic Telescope (LAMOST, also called Guo Shou Jing Telescope) is a National Major Scientific project undertaken by the Chinese Academy of Science (Wang et al 1996;Cui et al 2012). LAMOST has a field of view as large as 20 square degrees, and at the same time a large effective aperture that varies from 3.6 to 4.9 m in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…The principal axis lengths of the elliptical clear aperture entrance pupil M1 are 2R 0 and 2R 0 / cos i. Such reflective Schmidt design geometries have been adopted for broad-band faint object spectrographs with aspherised gratings [21] and also for the giant Chinese segmented telescope LAMOST [22,23]. However, in these cases, the focal surface in the middle of the beam creates a central obscuration and additional diffraction spikes are caused by the holding spider.c Therefore, in our proposed design, both the spiders and the corresponding diffractive deformation of the PSF are eliminated by adding a folding flat mirror.…”
Section: Bi-folded Schmidt Design a The Design Conceptmentioning
confidence: 99%